Penerapan Peraturan Mahkamah Agung Republik Indonesia Nomor 3 Tahun 2017 Tentang Pedoman Mengadili Perkara Perempuan Berhadapan dengan Hukum di Pengadilan Negeri Marisa - Sasongko, Catyawi Avesta; Akili, Rustam Hs.; Ismail, Nurwita; Moonti, Roy Marthen; Bunga, Marten (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to determine the application of Supreme Court Regulation No. 3 of 2017 concerning Guidelines for Adjudicating Cases of Women Against the Law in Marisa District Court of Pohuwato Regency and to determine the obstacles faced by judges in the implementation of Supreme Court Regulation No. 3 of 2017 concerning Guidelines for Adjudicating Cases of Women Against the Law in the jurisdiction of Marisa District Court of Pohuwato Regency. The implementation of this research uses empris research. In this study, researchers used qualitative methods. The implementation of Supreme Court Regulation Number 3 of 2017 concerning guidelines for adjudicating cases of women facing the law Perma number 3 of 2017 is a significant effort in improving justice for women in the Indonesian justice system. The application of these guidelines in the Marisa District Court demonstrates a commitment to respect and protect women's rights. However, the implementation still faces challenges such as a lack of understanding and awareness of judges about gender issues as well as technical obstacles in the implementation of these guidelines. in the sense that the PERMA is still ineffective in its implementation. Although the Marisa District Court has also been running according to trial procedures.